Stalins Witnesses - Wachtel J.; Wachtel Julius (London New York Knox Robinson Publishing, 2013)
Vilna, the Russian Empire, 1905. En route to deliver a secret pamphlet entrusted to him by his older brothers, a boy falls into the clutches of the Czars secret police. Another decade will pass before the Crown gives way, not to liberally minded revolutionaries like Vladimir Romm but to the pitiless disciples of an embittered lawyer named Lenin. For the next three-quarters of a century Marxism, in its cruelest form, will rule Russia. As World War I yields to an uneasy peace, Romm joins Soviet intelligence. In 1934 he is named Izvestias inaugural correspondent to Washington and strives to bring key Americans to the Soviet side. But as Romms career reaches its zenith he is suddenly recalled, arrested, and forced to serve with four others as "witnesses" at the notorious 1937 Moscow show trial.
Keywords: 82-3 (NhUDOVNQ PROZAs